The Effect Of Education Game Of Ladder And Flashcard Media To Improve Reproduction Knowledge In Early Adolescents - Nurhidayat Ika Zahni; Hasnah Hasnah; Arbianingsih Arbianingsih (Universitas STRADA Indonesia, 2020)
This study aims to determine the effect of educational games media snakes and ladders flashcards to improve reproductive knowledge in early adolescents. This study uses a Quasi Experiment Design research design with a Pre test approach- Post test control group design. The number of samples in this study were 38 respondents consisting of 19 interventions and 19 controls. The sampling technique uses purposive sampling. The data collection tool uses a knowledge questionnaire of 15 questions. Data analysis uses the Wilcoxon Test statistic. The results of the study for the intervention group obtained values ​​(p = 0,000) or p <0.05 and for the control group obtained values ​​(p = 0.001) or p <0.05. So, the effect of snake ladder educational game media and flashcard between the intervention group and the control group were equally influential, however, the intervention group had a more significant influence compared to the control group